USE OF TIKTOK SOCIAL MEDIA IN CONTENT PREACHING TGH. LALU AHMAD ZAENURI - Sahril Halim; Mohammad Alawi (TASAMUH : Jurnal Komunikasi dan Pengembangan Masyarakat Islam, 2025)
The rapid development of digital technology and social media has significantly transformed communication patterns in society, including Islamic preaching (da’wah) activities. TikTok, as a short-video–based social media platform, offers great potential for disseminating Islamic values in an effective and wide-reaching manner. This study aims to analyze the utilization of TikTok as a medium for spreading Islamic values through the da’wah content of Tuan Guru Haji (TGH.) Lalu Ahmad Zaenuri. This research employs a qualitative approach using qualitative content analysis. The data were collected through non-participant observation and documentation of ten selected da’wah videos from the TikTok account @TuanGuruZaenuri. Data analysis was conducted using the Miles and Huberman model, which includes data reduction, data display, and conclusion drawing. The findings reveal that TGH. Lalu Ahmad Zaenuri effectively utilizes TikTok as a da’wah medium by presenting concise, communicative, and contextually relevant messages aligned with everyday life. The Islamic values conveyed encompass aspects of faith (aqidah), worship (ibadah), morality (akhlaq), social values, and spirituality. The use of simple language, occasional incorporation of the local Sasak language, and diverse preaching locations serve as distinctive characteristics that enhance audience engagement. Furthermore, TikTok’s interactive features enable two-way communication and facilitate the formation of digital religious communities. This study concludes that TikTok functions not only as an entertainment platform but also as an effective medium for Islamic da’wah in the digital era.